18F-FDG PET/CT in cyst infection in autosomal dominant polycystic kidney disease - Prabhu, Meghana; Damle, Nishikant A; Ray, Animesh; Kandasamy, Devasenathipathi (Indian Journal of Radiology and Imaging, 2020)
Infection of a cyst within an autosomal dominant polycystic kidney disease (ADPKD) is a serious complication. Diagnosis with conventional imaging techniques such as ultrasonography, computed tomography (CT), and magnetic resonance imaging can be sometimes challenging. The definite diagnosis is analysis of the cyst fluid, but cyst punctures can cause bleeding, rupture, and contamination of adjacent cysts. Recently, FDG PET/CT has been reported as a sensitive tool for detection of cyst infection. We describe a case of 63-year-old woman with infected cysts in the left kidney, in whom accurate diagnosis was made on FDG PET/CT. FDG PET/CT is an important investigation in patients with fever of uncertain etiology, where renal cyst infection is a possible cause, but other etiologies also need to be ruled out.
Keywords: Autosomal dominant polycystic kidney disease; FDG PET/CT; renal cyst infection